Pediatric perioperative outcomes: Protocol for a systematic literature review and identification of a core outcome set for infants, children, and young people requiring anesthesia and surgery. Issue 4 (17th February 2020) - Razavi, Cyrus; Walker, Suellen M.; Moonesinghe, S. Ramani; Stricker, Paul A.
Abstract: Clinical outcomes are measurable changes in health, function, or quality of life that are important for evaluating the quality of care and comparing the efficacy of interventions. However, clinical outcomes and related measurement tools need to be well‐defined, relevant, and valid. In adults, Core Outcome Measures in Effectiveness Trials (COMET) methodology has been used to develop core outcome sets for perioperative care. Systematic literature reviews identified standardized endpoints (StEP) and valid measurement tools, and consensus across a broader range of relevant stakeholders was achieved via a Delphi process to establish Core Outcome Measures in Perioperative and Anaesthetic Care (COMPAC). Core outcome sets for pediatric perioperative care cannot be directly extrapolated from adult data. The type and weighting of endpoints within particular domains can be influenced by age‐dependent differences in the indications for and/or nature of surgery and medical comorbidities, and the validity and utility of many measurement tools vary significantly with developmental stage and age. The involvement of parents/carers is essential as they frequently act as surrogate responders for preverbal and developmentally delayed children, parental response may influence child outcome, and parental and/or child ranking of outcomes may differ from those of health professionals. Here, we describe the formation of the international Pediatric Perioperative Outcomes Group, which aims to identify and create validated, broadly applicable, patient‐centered outcome measures for infants, children, and young people. Methodologies parallel that of the StEP and COMPAC projects, and systematic literature searches have been performed within agreed age‐dependent subpopulations to identify reported outcomes and measurement tools. This represents the first steps for developing core outcome sets for pediatric perioperative care.